Can Calcium Propionate Help Maintain Calcium Concentrations and Prevent Metritis in Dairy Cows with Dystocia? - Klibs N. Galvao; Mauricio Benzaquen; Carlos A. Risco (EDIS)
Studies have suggested that giving dairy cows supplemental calcium may reduce the incidence of metritis. This study tested this hypothesis with cows at the UF Dairy Unit and found that calcium supplements actually did not benefit postpartum health and are not recommended as means of metritis prevention. This 3-page fact sheet was written by Klibs N. Galvao, Mauricio Benzaquen, and Carlos A. Risco, and published by the UF Department of Veterinary Medicine—Large Animal Clinical Sciences, June 2015.